2014
DOI: 10.5005/jp-journals-10016-1087
|View full text |Cite
|
Sign up to set email alerts
|

Role of Midtrimester Localization of the Placenta in predicting Pregnancy Outcome

Abstract: The localization of the placenta by ultrasound in the second trimester has been hypothesized to have an impact on the pregnancy, in terms of antenatal, intrapartum and postnatal outcome. Objective To evaluate the role of placental location in predicting the pregnancy outcome. Materials and methods It was a prospective observational study conducted between September 2011 and March 2013 at a tertiary care hospital. Placental location, as determined by midtrimester ultrasound in 620 antenatal women, was divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Faizi S et al, conducted a prospective study on 620 women and placental location was determined by USG. 2 Placental location was divided into 5 groups -anterior, posterior, fundal, low lying depending on where > 75% of placental mass is located. 274 (44.1%) had anterior, 169 (27.2%) had posterior,98 (15.8%) had central, 61 (9.8%) had lateral and 18 (2.9%) had placenta praevia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faizi S et al, conducted a prospective study on 620 women and placental location was determined by USG. 2 Placental location was divided into 5 groups -anterior, posterior, fundal, low lying depending on where > 75% of placental mass is located. 274 (44.1%) had anterior, 169 (27.2%) had posterior,98 (15.8%) had central, 61 (9.8%) had lateral and 18 (2.9%) had placenta praevia.…”
Section: Discussionmentioning
confidence: 99%
“…In women with centrally located placentas, both uterine arteries demonstrate similar resistance. 1,2 Thus, there is overall increase in resistance of placental vascular bed. Women with laterally located placenta are thus more prone to have foetuses with IUGR, IUFD and LBW.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Faizi et al studied 620 pregnant women, 44.1% had anterior, 27.2% had posterior, 15.8% had fundal, 9.8% had lateral placentae and 2.9% had placenta previa as per the last scan done at 28 weeks. 17 Pre-eclampsia (27.9%) and antepartum hemorrhage (19.7%) were more common in lateral placenta whereas term prelabor rupture of membranes (11.2%) was more common in fundal placenta and these findings were statistically significant. The incidence of IUGR was also found to be higher in patients with lateral (16.4%) and posteriorly (16%) implanted placenta although there was no statistically significant association.…”
Section: Resultsmentioning
confidence: 89%
“…However, in a study by Magann, no significant association was found between placental location and low APGAR scores Table 4. 12,13 Incidence of NICU admission was more for babies of the mother who had preeclampsia and also women with the lateral placenta. It was seen that babies of 13 (24.52%) women with preeclampsia and 35 (10.17%) normotensive women required NICU admission.…”
Section: Title Of Research Project: Placental Laterality As Predictor Of Preeclampsia: a Prospective Studymentioning
confidence: 99%